Seleção de genótipos de trigo visando à tolerância ao estresse por encharcamento - Kavalco, Sydney Antonio Frehner (2013)
Flooding, as well as salinity, drought, toxicity (Na, Fe, Al, B, Mn) and freezing are the main abiotic stressors that restrict the growth and development, promoting the expression reduction of the genetic potential in plants. The physiological responses of sensitivity to stress are differently reported, and flooding tolerance may vary from only a few hours to several days or weeks. This time difference is given by the structural differences possibilities among species, by number of tillers per plant, by specific tissues directly affected, by the development stage and the temperature conditions of cultivation. The tillering is one of the three main components of grain yield in cereals and is determined by the capacity of the plant has to produce and fill the ears. Is closely linked to the ability of plants have to tolerate the flooding stress. Flooded soils are present in several Brazilian states. Only in Rio Grande do Sul are 5.4 million ha of flooded soils, from these around 1 million ha is used to produce rice, the rest of these area remains under-utilized for the cereal production. In this scenario the pursuit of better adapted cultivars to flooding stress, has very importance due to the need for more productive, tolerant and more competitive genotypes with a better relation of cost and crop production. In this work 15 segregating populations and six wheat cultivars were evaluated for tolerance to flooding stress, in the years 2010, 2011 and 2012. The objective of this study was to identify the effectiveness of pedigree method for selection in flooded soils, if there is genetic variability for flooding tolerance in wheat, the effect of stress on grain yield and cycle traits and what are the best parents in respect to segregating populations by combining ability of each genotype. Statistical analyzes of data were performed using the programs GENES (CRUZ, 2006) and R (CORE TEAM, 2012), using analysis of variance, data normality, average test by Tukey method at 5% of significance level, estimating the general and specific combining abilities for each genotype and canonical variable analysis. The results indicate that the flooding stress in wheat is closely linked to the ability of the plants have to detect and respond to the stress stimulation, statistically significant differences were found for grain yield and cycle traits. The parents who had higher general combining ability were BRS177, Figueira and IPR85. The most promising genotypes for selection to flooding tolerance are represented by populations 02 (Juriti x IPR85), 07 (CEP29 x BRS177), 08 (CEP29 x Safira), 12 (Figueira x IPR85) 13 (BRS177 x Safira) and 14 (BRS177 x Figueira) with greater emphasis on the populations 02, 13 and 14.